2006
DOI: 10.1007/s00380-005-0854-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetylcysteine on oxidative stress and ventricular function in patients with myocardial infarction

Abstract: Recent evidence suggests that postischemic myocardial dysfunction ("stunning") may be mediated by oxygen free radicals. Various studies have reported the beneficial effects of antioxidants in ischemia-reperfusion injury. The aim of this study was to assess the effect of N-acetylcysteine (NAC) treatment on oxidative stress, infarct size, and left ventricular (LV) function, as adjunct therapy in myocardial infarction (MI). Patients with acute MI received either 15 g NAC infused over 24 h (n = 15) or no NAC (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 24 publications
1
28
0
4
Order By: Relevance
“…Similarly to our findings, intravenous NAC has a tendency to increase blood pressure and heart rate in piglets during hypoxia-reoxygenation, but it takes several hours for these parameters to return to the level comparable with that in sham-treated animals (Liu et al 2010). Improved function of the left ventricle after NAC has been found also in patients with myocardial infarction (Yesilbursa et al 2006). In the meconium-instilled animals of the present study we found a higher plasma aldosterone level compared with that in the salineinstilled animals.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to our findings, intravenous NAC has a tendency to increase blood pressure and heart rate in piglets during hypoxia-reoxygenation, but it takes several hours for these parameters to return to the level comparable with that in sham-treated animals (Liu et al 2010). Improved function of the left ventricle after NAC has been found also in patients with myocardial infarction (Yesilbursa et al 2006). In the meconium-instilled animals of the present study we found a higher plasma aldosterone level compared with that in the salineinstilled animals.…”
Section: Discussionsupporting
confidence: 88%
“…However, it also led to a more heterogeneous appearance of the infarcts with increased ventricular arrhythmias (26). In addition, there are several positive effects on platelet and vascular function (27,28). Similar to several previous trials of reperfusion injury reduction, translation of these beneficial effects into the clinical setting has been disappointing (4).…”
Section: Magnetic Resonance Resultsmentioning
confidence: 99%
“…It is not possible to exclude that all these aspects may be related to the high prevalence of inflammatory gene polymorphism demonstrated in these young subjects with AMI. [35][36][37][38][39] The persistence of an impaired oxidative stress 12 months after AMI requires 2 different considerations: first, the use of antioxidant therapy after AMI may be advisable [40][41][42][43] ; moreover, the altered oxidative status observed much later after AMI may be present also before AMI. Regarding this latter aspect, our project of reevaluating the same AMI subjects 2 years or even later after AMI may give further information.…”
Section: Discussionmentioning
confidence: 99%